Significance of Syndrome Teetering in Development of Residual Pain Syndrome in Patients Operated for Lumbar Osteochondrosis (Texas Journal of Multidisciplinary Studies, 2022)
It is known that the problems of osteochondrosis of the spine acquire both medico-social and economic importance, since the disease in some cases leads to a decrease in productivity, and sometimes to disability of people of working age. In addition, a decrease in the quality of life, an increase in the incidence and rejuvenation of it from year to year, the lack of effective conservative and surgical methods of treatment, the frequent chronicling of acute root pain syndrome, the development of residual pain syndrome in 30- 50% of promptly treated patients testifies to the unsolved problem of pathogenesis and pathogenetic surgical method of treating lumbar osteochondrosis.